2019
DOI: 10.1016/j.exer.2018.11.012
|View full text |Cite
|
Sign up to set email alerts
|

Effect of diabetes and hyaluronidase on the retinal endothelial glycocalyx in mice

Abstract: We sought to investigate the effects of diabetes and hyaluronidase on the thickness of the endothelial glycocalyx layer in the mouse retina. In our study, the retinal circulation of diabetic Ins2(Akita) mice and their nondiabetic littermates were observed via intravital microscopy. The endothelial glycocalyx thickness was determined from the infusion of two fluorescently labeled plasma markers, one of which was a high molecular weight rhodamine dextran (MW=155,000) excluded from the glycocalyx, and the other a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 18 publications
1
14
0
Order By: Relevance
“…DR is characterized by microaneurysms, leukocyte-endothelial adhesion, hemorrhage, capillary occlusion, neovascularization, and increased permeability. 51 Diabetic rats have a significantly thinner retinal endothelial glycocalyx compared with control rats (28.3 versus 60.2 nmol/L, P < 0.01), measured using transmission electron microscopy. 52 In addition, in the Akita mouse model of type 1 diabetes, anesthetized diabetic mice have a significantly thinner glycocalyx in retinal arterioles.…”
Section: Diabetic Retinopathymentioning
confidence: 87%
“…DR is characterized by microaneurysms, leukocyte-endothelial adhesion, hemorrhage, capillary occlusion, neovascularization, and increased permeability. 51 Diabetic rats have a significantly thinner retinal endothelial glycocalyx compared with control rats (28.3 versus 60.2 nmol/L, P < 0.01), measured using transmission electron microscopy. 52 In addition, in the Akita mouse model of type 1 diabetes, anesthetized diabetic mice have a significantly thinner glycocalyx in retinal arterioles.…”
Section: Diabetic Retinopathymentioning
confidence: 87%
“…In hyperglycemic and/or inflammatory environments, hyaluronidase expression is upregulated, cutting the glycocalyx and producing hyaluronic acid fragments. Previous studies found that hyaluronic acid and hyaluronidase activity are increased in the serum of diabetics patients (Nieuwdorp et al, 2006a) and mice (Ikegami-Kawai et al, 2003;Leskova et al, 2019). Increased plasma hyaluronic acid and hyaluronidase activity were detected in both human Type 1 (Nieuwdorp et al, 2006a) and Type 2 (Broekhuizen et al, 2010) diabetes.…”
Section: Hyaluronidasementioning
confidence: 86%
“…Leskova et al . 106 investigated the effects of diabetes and HYAL1 on the thickness of the GCX in the mouse retina. The retinal circulation of diabetic Ins2 (Akita) mice and their nondiabetic littermates were observed via intravital microscopy.…”
Section: Part B: the Role Of The Glycocalyx In Vascular Related Diseamentioning
confidence: 99%